BAC TRAT 2A® biological modulator performed well in the control of Salmonella sp. in production environment and digestive tract of broilers - Gabriela Gheller Kaefer, Bruna; Aparecida Rodrigues dos Santos, Emanoelli [UNESP]; Ereno Tadielo, Leonardo [UNESP]; Henrique Bellé, Thiago; Arruda Schmiedt, Jhennifer; Henrique Silva Orisio, Paulo; Luiz Richter, Jeferson; Pires Simões, Eduarda; Camilo Alberton, Geraldo; Cunha Barcellos, Vinicius; Viana, Cibeli; dos Santos Bersot, Luciano (Elsevier, 2022)
Biological methods such as the use of competitive and beneficial microorganisms that hinder microbial survival have been gaining prominence in the poultry industry, with a view to reducing contamination by pathogens of importance in the sector, such as Salmonella sp. The objectives of this study were to evaluate the effect of the biological modulator BAC TRAT 2A® on the reduction of Salmonella sp. in the poultry beddingand in the gastrointestinal tract of broilers under real housing conditions subject to natural infection by the pathogen, as well as to evaluate the genotypic and phenotypic profile of the isolates obtained. The experiment was carried out between March 2018 and August 2019, in the state of Paraná. The study consisted of two sheds, the bed used in shed 1 being the negative control (C) and the bed in shed 2 being the treatment (T), being treated with the biological modulator BAC TRAT 2A®. The performance of BAC TRAT 2A® was positive for reducing the health challenge involving the presence of Salmonella sp. during poultry farming. Both in the environment and in the birds 'cecum there was a decrease in the pathogen load, mainly in the final stages of the breeding cycle, possibly caused by the competitive exclusion in the aviary litter and biological modulation of the birds' microbiota in contact with the product.
Keywords: Biological modulator; Health challenge; Poultry industry; Salmonellosis